Evaluating surface water and groundwater quality parameters in the Karst Mining Zone, Gunungkidul for environmental risk mitigation - Yudhistira Zein Sanadha; Haerul Anwar; Faisal M. Jasin; Bayu Achil Sadjab (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2025)
This study aims to characterize the physical, chemical, and microbiological water parameters of the Oya River (Bleberan Playen) and groundwater in the CV Kusuma Arga monitoring well, located in the white stone mining zone, Ponjong District, Gunungkidul Regency, Special Region of Yogyakarta, Indonesia. The importance of this research is driven by the lack of comprehensive water quality data in active karst mining areas and the potential environmental and health risks associated with contamination. Parameters tested included temperature, electrical conductivity (EC), total dissolved solids (TDS), turbidity, pH, nitrite, ammonia, chloride, sulfate, detergents, dissolved iron, dissolved lead, dissolved copper, dissolved cadmium, dissolved manganese, dissolved nickel, total coliform, and fecal coliform. Testing methods referred to the Indonesian National Standard (SNI) and Standard Methods, including the use of atomic absorption spectrophotometry (AAS) for heavy metal analysis and the membrane filter method for microbiology. The test results showed that most physical and chemical water parameters from both sources met the relevant quality standards. For example, the well water temperature of 27°C and well water pH of 6.9 were both declared to be by standards. However, analysis showed lead concentrations (0.1 mg/l in the river) and cadmium (0.010 mg/l in the river) exceeding World Health Organization (WHO) recommendations for drinking water, although initially categorized as